PENGARUH COMPANY SIZE, PROFITABILITAS, LEVERAGE, CAPITAL INTENSITY DAN LIKUIDITAS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2015-2019 - Anissah Naim Fatimah; Siti Nurlaela; Purnama Siddi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study animed to determinant the effect of company size, profitability, leverage, capital intensity and current ratio on tax avoidance. This Type of research is kuntitatif. Population in this research of manufacturing companies in the consumer goods industry sector of the food and beverage sub-sector which were listed on Indonesia Stock Exchange (IDX)for the 2015-2019 period. The sample are choose from purposive sampling method and get sample of 12 companies based on some criteria. Data source is secondary data obtained from website (www.idx.co.id). This study uses multiple analysis regression to analyze data with SPSS 25 version edition program. Result of this research showed that company size has influence on tax avoidance. This is evidenced by the results of the value of tsig 0.000 ≤ 0.05. While profitability has no influence on tax avoidance. This is evidenced by the results of the value of tsig 0.309 > 0.05. Leverage has no influence on tax avoidance. This is evidenced by the results of the value of tsig 0.439>0.05. Capital intensity has no influence on tax avoidance. This is evidenced by the results of the value of tsig 0.086 > 0.05 . Current ratio has no influence on tax avoidance. This is evidenced by the results of the value of tsig 0.829 > 0.05.